Pengembangan Buku Pengayaan Cerita Rakyat Jepara Bermuatan Nilai Humanis bagi Peserta Didik SMP - Melly Vila Melani; U’um Qomariyah (Jurnal Pendidikan Bahasa dan Sastra, 2022)
This study aims to produce an enrichment book of Jepara folklore containing humanist values for junior high school students. This study uses the Research and Development (RnD) research method which is then adapted to the needs of the researcher. The researcher's needs include five stages, namely: (1) potential and problem collection, (2) data collection, (3) product design, (4) design validation, and (5) design revision. Collecting data using literature study techniques, interviews, needs questionnaires for students and educators, as well as prototype validation questionnaires. Data analysis used descriptive qualitative, namely data exposure and data conclusions. The Jepara folklore enrichment book containing humanist values got the average score from the validator, namely: (1) The content/material aspect got an average score of 83.33% with a very decent category, (2) the presentation aspect got an average score of 79 .16% so that it falls into the very feasible category, (3) the language and readability aspects get an average score of 82.25% with a decent category, and (4) the graphic aspect gets a perfect average score of 100% so that it is included in the very category. feasible. The prototype of the enrichment book was developed into three main parts, namely the introduction, the content, and the closing section. Based on the assessments carried out by two expert validators in the field of literature and the field of book writing, the Jepara folklore enrichment book containing humanist values for junior high school students is very appropriate and attracts students' interest in exploring folklore material.